Clinical and microbiological characteristics and outcome of patients with healthcare associated ventriculitis and meningitis at a Public Sector Hospital in Pakistan - Arshad, Nazish; Samad, Saima; Memon, Sughand; Ishaque, Sadia; Baqi, Shehla (Infectious Diseases Journal of Pakistan, 2024)
Background: Healthcare-associated meningitis and ventriculitis (HAVM) is a serious complication of placement of ventriculoperitoneal shunt (VPS) and external ventricular device (EVD), and can incur high morbidity and mortality. Material And Methods: This retrospective descriptive, single center study was conducted in patients who had placement of VPS or EVD between January 2018 and December 2021 and developed HAVM. A list of these patients was retrieved from records maintained by the neurosurgery department. Results: Thirty patients with HAVM were included. Median age was 8.5(IQR 22.25-0.75), two thirds were pediatric, 50% were males. Indication for device placement was congenital hydrocephalus in 18 (60%), tumor in 6 (20%) with VPS insertion in 25 (83.3%), EVD in 5 (16.7%). Fever was documented in 29 (96.7%). Cerebrospinal fluid analysis (CSF) demonstrated median pleocytosis with IQR of 93.5 (17-12959), protein of 131 (IQR 2-285), glucose of 24.5 (IQR 0-72). 17 (56.6%) had ICU stay, 11 were on mechanical ventilation. Mortality occurred in 4 (13.3%). CSF cultures were positive in 28 (93%) patients. Of 32 bacterial isolates, 16 were gram positive and 16 gram negative. In 15 (93.7%) patients, gram negatives were resistant to carbapenems and included 7 (46.6%) Enterobacterales (CRE), 3 (20%) Pseudomonas aeruginosa and 5 (33.3%) Acinetobacter spp. They were treated with IV colistin and meropenem. Predictors of mortality were male sex and sepsis. (p ≤ 0.05). Conclusion: Male sex and sepsis were found to be predictors of mortality in HAVM. Gram-negatives in CSF cultures of 15 (93.7%) patients were resistant to carbapenems and challenging to treat. Keywords: Cerebrospinal fluid infection, Healthcare-associated meningitis and ventriculitis, Hydrocephalus management, Risk-factors, Shunt infections